Transcranial direct current stimulation neuromodulates intracranial cognitive evoked activity in humans - Mireille Tabikh; Tom Quetu; Louis Maillard; Sophie Colnat-Coulbois; Bruno Rossion; Laurent Koessler (Proceedings of the National Academy of Sciences, 2025)
Transcranial direct current stimulation (tDCS) is an easy to use, noninvasive brain stimulation technique that gained prominence for its potential in cognitive rehabilitation. Electroencephalography (EEG), which records electrical brain activity with a high temporal resolution, is well suited to quantify tDCS-induced neuromodulation in humans. However, most studies relying on scalp EEG recordings or event-related potentials showed low reliability and only indirect correlations. Here, we combined intracranial EEG (iEEG) recordings with a sham-controlled tDCS experiment during fast periodic visual stimulation. Anodal (+2 mA) tDCS was applied over the right occipito-temporal cortex for 20 min using two small ring high-definition electrodes. Through the analysis of iEEG signals of 947 intracerebral contacts in 11 drug-resistant epileptic patients, we quantified the neuromodulation of iEEG cognitive evoked responses during (P2 phase) and after (P3 phase) tDCS by comparison to a control phase before tDCS (P1 phase). Significant neuromodulations of face-selective iEEG activity in anterior & posterior temporal lobe and in the occipital lobe were found, with amplitude increases of 3% and 4%, 16% and 13%, and 36% and 33%, during and after tDCS, respectively. Interestingly, despite a unique tDCS session, the face-selective neuromodulation in the right visual occipito-temporal cortex remained significant ( P = 0.015) after tDCS (P3 vs. P1). This iEEG study demonstrates that using low intensity tDCS and small ring electrodes can induce significant electrophysiological effects on a selective cognitive function in humans.